Digital Financial Inclusion and MSME Resilience in Post-Pandemic Indonesia: An Empirical Analysis of Fintech Adoption and Business Sustainability - Pratama, Rafiq Aditya; Azzahra, Salsabila Nur (Jurnal Ekonomi, Manajemen, dan Bisnis, 2026)
This study analyzes the relationship between digital financial inclusion, fintech adoption, MSME resilience, and business sustainability in post-pandemic Indonesia. Micro, Small, and Medium Enterprises play a central role in Indonesia’s economic structure, yet they experienced significant financial vulnerability during the COVID-19 crisis. The research applies a quantitative explanatory design using a cross-sectional survey of 312 MSME owners across manufacturing, trade, and service sectors. Data were analyzed using Partial Least Squares Structural Equation Modeling to examine direct and mediated relationships among variables. The findings indicate that fintech adoption significantly strengthens digital financial inclusion. MSMEs that actively use digital payments, mobile banking, and peer-to-peer lending demonstrate broader access to formal financial services. Digital financial inclusion significantly enhances MSME resilience by improving liquidity stability, adaptive capacity, and revenue recovery speed. Resilience, in turn, strongly influences long-term business sustainability. Mediation analysis confirms that digital financial inclusion partially mediates the relationship between fintech adoption and resilience. This result suggests that fintech usage alone is insufficient to generate sustainable outcomes unless it translates into meaningful financial participation. The study concludes that strengthening digital financial inclusion is critical for reinforcing MSME resilience and sustainability in Indonesia’s post-pandemic economy. Policy strategies should prioritize digital infrastructure expansion, financial literacy development, and supportive regulatory frameworks to maximize fintech benefits for MSMEs.